Multiple Access Communcations 6th International Workshop, MACOM 2013, Vilnius, Lithuania, December 16-17, 2013. Proceedings - Jonsson, Magnus; Vinel, Alexey; Bellalta, Boris; Marina, Ninoslav; Dimitrova, Desislava; Fiems, Dieter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 6th International Workshop on Multiple Access Communications, MACOM 2013, held in Vilnius, Lithuania, in December 2013. The 16 full papers presented were carefully reviewed and selected from various submissions. They describe the latest advancements in the field of multiple access communications with an emphasis on OFDM techniques, channel coding, spectrum management, medium access control protocols and different aspects of wireless access networks.
Latest advancements in the field of multiple access communications with an emphasis on OFDM techniques -- Channel coding -- Spectrum management -- Medium access control protocols and different aspects of wireless access networks.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information Systems; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems; Software Engineering; Computers and Society